Deep Time in the Nineteenth-Century British Novel: Temporality, Science, and Literary Form - Isaacson, Kja (Université d'Ottawa / University of Ottawa, 2017)
This dissertation examines representations of deep time in nineteenth-century British novels in order to argue that these texts help carve a path for our contemporary definitions of deep time and the Anthropocene. Examining fiction by Charles Dickens, George Eliot, Thomas Hardy, Edward Bulwer-Lytton, H. Rider Haggard, H. G. Wells, and Joseph Conrad, I suggest that these novels participate in the secularization of deep time by transforming the concept of vast spiritual time that had been in use earlier in the nineteenth century into a scientifically-informed model that anticipates our current understandings of deep time. While the concept of geological time emerged in the late-eighteenth century and became widely recognized in the nineteenth, the phrase “deep time” originates in nineteenth-century literature when Thomas Carlyle first used it in a non-scientific context. By studying a wide range of fiction, I demonstrate how nineteenth-century authors employed innovative narrative strategies to convey these potentially inconceivable timescales in non-numerical terms, and thereby make them more accessible to human comprehension. I also challenge conventional distinctions between literary realism and popular romance in the period by analyzing the complementary ways in which both genres of fiction engage with vast temporal scales in their narratives. I develop my argument by examining how these novels use a model of what I call “folding time” to incorporate remote time periods into their texts. Departing from the novel’s linear narrative structure to bring distant historical moments into direct contact with one another, folding time situates human activity in relation to vast pre-and-post-human periods and in doing so acknowledges an age of humans within deep time; in this sense, these novels articulate an early concept of the Anthropocene. By including deep time in the novel’s traditionally individual and familial framework, these authors simultaneously expand the novel’s temporal scope and humanize vast scientific timescales. Further, as these novels illustrate characters’ psychological responses to overwhelming scientific timescales, they reposition deep time in relation to private temporal experience. This study employs an interdisciplinary approach to acknowledge the mutually reciprocal relationship between science and literature in the nineteenth century, and draws on temporality studies, history of science theory, and literary criticism to situate its argument in relation to current critical discussions. I also consider the work of scientists such as Charles Lyell, Charles Darwin, and William Thomson in order to contextualize my novels’ scientific references. By studying nineteenth-century British novels in relation to scientific temporalities, this dissertation recovers an overlooked component of the history of deep time that has had significant and lasting cultural influence given the enduring popularity and wide readership of these texts.
Keywords: Deep Time; Nineteenth-Century Literature; Temporality; Science; Anthropocene; Novel; Carlyle; Dickens; Eliot; Hardy; Bulwer; Haggard; Wells; Conrad; Darwin; History of Science; Lyell; Thomson; Victorian Literature; Literary Form; Genre